WAYS TO DEVELOP THE COMMUNICATIVE AND SPEECH COMPETENCE OF FUTURE PRIMARY EDUCATION TEACHERS - M. S. Akhmedova (Journals Park Publishing, 2022)
This article highlights the issues of trends in the development of communicative and speech competence of teachers, teachers in the system of continuing education, the concepts of professional competence and competence-based approach to learning are given. According to the author, communicative-speech, information competencies are one of the important components of a specialist's professional competence. The article also highlights the main factors contributing to the formation of communicative and speech competence and professional growth of the teacher.